Management of dental disease in eared seals (family Otariidae): a Delphi approach - Simeone, Claire A.; Schwitzer, Nora; Johnson, Shawn P.; Almansa Ruiz, José C.; Debosschere, Yves; Force, Judy; Forsayeth, Aaron; Gawor, Jerzy P.; Gracis, Margherita; Holmstrom, Steven; Legendre, Loïc; Mestrinho, Lisa A.; et al. (Frontiers in Veterinary Science, 2025)
ObjectivePublished literature is sparse on topics associated with eared seal (otariid) dentistry. The objective of this study was to establish consensus on effective management of dental disease in otariids, using a Delphi approach.MethodsA total of 25 veterinarians with experience managing dental disease in seven species of otariids participated in the Delphi process.ResultsOral lesions and their contributing risk factors were ranked according to perceived frequency. Consensus statements for best practices were agreed upon for a variety of topics within the categories of planning and preparation, procedural details, intervention strategies, and postoperative care. Panelist comments were collated into a Supplementary File to assist clinicians in forming their own conclusions on topics for which no consensus yet exists.ConclusionOpportunities for future research include factors associated with oral lesions, ideal anesthetic management, identification of ideal candidates for endodontic therapies, ideal local and regional anesthesia, ideal suture and closure techniques, particularly with the goal of reducing dehiscence as a postoperative complication, and ideal postoperative care options.